Pemodelan dan Simulasi Monte Carlo dalam Meningkatkan Pendapatan Penjualan Peralatan Motor - Wita Siska Moza (Jurnal Informatika Ekonomi Bisnis, 2020)
AMI Motor shop is a various shop that is engaged in sales by selling various motorcycle equipment. Sales transactions vary in stores, but almost all products have increased and decreased, so it is necessary to know how the product data is related to consumer demand. Sales simulation is an estimate that can provide benefits in making decisions to increase sales revenue. The purpose of this study is to predict what motorcycle equipment stock should be increased and decreased in sales in the following year. The data used is motor equipment sales data in 2018 and 2019 which are processed using the Monte Carlo method. In speeding up data processing, this system is applied to a web-based system using the PHP (Hypertext Processor) programming language. Based on the results of testing prediction levels of motorcycle equipment sales, average accuracy is 95,92%, making it easier for company leaders to make decisions on developing business strategies to increase sales revenue.